2015
DOI: 10.4238/2015.october.26.11
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of BRCA1/2 gene and pathologic characteristics from Kazakh population with sporadic breast cancer in northwestern China

Abstract: ABSTRACT. Mutations in the BRCA1/2 genes are associated with an increased risk of breast cancer, but no large-scale research have examined the BRCA1/2 mutations in Chinese Kazakh women. We evaluated the frequency and distributions of BRCA1 and BRCA2 gene mutations in Kazakh sporadic breast cancer patients and healthy women in China. The association between the clinical-pathologic features of Kazakh breast cancer patients and BRCA1/2 mutations were also investigated. Two unclassified variants (T539M and T1915M)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Zhang G et al found that compared with the white, the expression of TP53 and AKT1 is higher in Chinese, which may be a potential factor affecting the incidence of BC [22]. Yang SY et al found that the morbidity of BC is different between China and other Asian populations, and the mutation frequency of BRCA2 was much higher than that of BRCA1, by comparison, BRCA1 mutations are more common than BRCA2 mutations in Caucasian populations [23]. Chen L et al researched the Asia and African Americans, discovering that there are more than 50% of BC cases in Asia were lumA subtype, and the basal-like subtype only accounts for 5%, however, in African-American populations, this subtype accounts for more than 30% [24].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang G et al found that compared with the white, the expression of TP53 and AKT1 is higher in Chinese, which may be a potential factor affecting the incidence of BC [22]. Yang SY et al found that the morbidity of BC is different between China and other Asian populations, and the mutation frequency of BRCA2 was much higher than that of BRCA1, by comparison, BRCA1 mutations are more common than BRCA2 mutations in Caucasian populations [23]. Chen L et al researched the Asia and African Americans, discovering that there are more than 50% of BC cases in Asia were lumA subtype, and the basal-like subtype only accounts for 5%, however, in African-American populations, this subtype accounts for more than 30% [24].…”
Section: Introductionmentioning
confidence: 99%
“…Yang SY et al found that the morbidity of BC is different between China and other Asian populations, and the mutation frequency of BRCA2 was much higher than that of BRCA1, by comparison, BRCA1 mutations are more common than BRCA2 mutations in Caucasian populations [23]. Chen L et al researched the Asia and African Americans, discovering that there are more than 50% of BC cases in Asia were lumA subtype, and the basal-like subtype only accounts for 5%, however, in African-American populations, this subtype accounts for more than 30% [24].…”
mentioning
confidence: 99%